2018
DOI: 10.5430/jha.v7n5p1
|View full text |Cite
|
Sign up to set email alerts
|

Measuring healthcare service quality in a private hospital in a developing country by tools of Victorian patient satisfaction monitor

Abstract: Objective: A survey was conducted for patient satisfaction (PS) in a private hospital in Hanoi, Vietnam using the Tools of Victorian Patient Satisfaction Monitor (VPSM) 2012. Methods: The study obtained feedbacks from patients from December 2013 to Jan 2014. After patients finished their outpatient care at the hospital, they were asked 25 questions following the VPSM. Each question can score from 1-5. Results: In total, 420 patients were interviewed and 396 patients completed the survey. Levels of customer sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…29 Several models of questionnaires and ways to assess client satisfaction in health care are disseminated internationally, such as the model used in Vietnam with 26 assessment items involving six aspects: access and admission, general patient information, treatment and related information, complaints management, physical environment and follow-up. 30 A study in China proposed an evaluation model and found that patient satisfaction was significantly affected by perceived quality, expectation and impact of the disease, hospital referral, and client complaints. 31 In validated instruments for the evaluation of client service satisfaction, with possibilities of adaptations, attention should be paid to the inclusion of elements focused on the evaluation of the experiences lived by them in the service situation, such as the form of reception; information and guidance received; trajectory through the various sectors; agility and resolution of the problems that led customers to the organization.…”
Section: Discussionmentioning
confidence: 99%
“…29 Several models of questionnaires and ways to assess client satisfaction in health care are disseminated internationally, such as the model used in Vietnam with 26 assessment items involving six aspects: access and admission, general patient information, treatment and related information, complaints management, physical environment and follow-up. 30 A study in China proposed an evaluation model and found that patient satisfaction was significantly affected by perceived quality, expectation and impact of the disease, hospital referral, and client complaints. 31 In validated instruments for the evaluation of client service satisfaction, with possibilities of adaptations, attention should be paid to the inclusion of elements focused on the evaluation of the experiences lived by them in the service situation, such as the form of reception; information and guidance received; trajectory through the various sectors; agility and resolution of the problems that led customers to the organization.…”
Section: Discussionmentioning
confidence: 99%
“…Patient satisfaction is "fulfillment of or meeting one's expectations about a service or product" (Chu and Khong, 2018;Vinodkumar et al, 2018). It has been argued that patients and their relatives expect good clinical care as well as good facilities during their visit to a hospital.…”
Section: Introductionmentioning
confidence: 99%